Transformasi Komunikasi Dakwah dan Pengaruhnya terhadap Praktik Keagamaan Masyarakat Muslim di Indonesia - Ulfa, Marwa (LAKPESDAM MWCNU Palengaan, 2024)
Effectiveness in conveying da'wah messages is also influenced by the media used by Da'i, especially in the digital era. The focus of the study in this research is the transformation of digital da'wah communication which has an impact on the religious practices of Indonesian society. The findings show a significant change in the methods and media of da'wah which are now dominated by digital platforms, such as social media and internet-based applications, which enable the delivery of religious messages to be more interactive and easily accessible. Apart from that, this transformation also creates a new interaction space where people can participate in direct religious discussions, connecting religious leaders and communities virtually. However, challenges to the authority and authenticity of religious messages on digital platforms need to be considered, considering the increasingly diverse content of preaching. The recommendation for further research is to be able to study it in more depth, such as a case study that focuses on the psychological impact of digitalization of preaching and transcendental communication among Muslims. Fokus kajian dalam penelitian ini adalah transformasi komunikasi dakwah digital berdampak pada praktik keagamaan masyarakat Indonesia. Hasil dari penelitian ini mendeskripsikan dan mengklasifikasikan berbagai bentuk pergeseran praktik keagamaan masyarakat Indonesia yang di sebabkan karena adanya perubahan dalam metode dan media dakwah yang kini didominasi oleh platform digital, seperti media sosial dan aplikasi berbasis internet, yang memungkinkan penyampaian pesan agama lebih interaktif dan mudah diakses. Selain itu, transformasi ini juga menciptakan ruang interaksi baru di mana masyarakat dapat berpartisipasi dalam diskusi keagamaan secara langsung, menghubungkan tokoh agama dan komunitas secara virtual. Namun, tantangan otoritas dan keaslian pesan agama dalam platform digital perlu diperhatikan, mengingat konten dakwah yang semakin beragam. Harapannya penelitian ini mampu meningkatkan khazanah pengetahuan umat muslim terutama di Indonesia.